Fulminant acute liver failure secondary to severe dengue in a child: case report - Domínguez-Rojas, Jesús (2024)
Dengue is a common infectious disease in tropical areas such as Peru. This virus can cause underreported and potentially fatal complications such as acute liver failure. We report the case of a 7-year-old boy who presented with fever, headache, and abdominal pain. On ultrasound, we found hepatomegaly and labs severe thrombocytopenia and elevated transaminases. During hospitalization he was diagnosed with severe dengue and developed acute liver failure, kidney injury, and encephalopathy. Although intensive care management and assisted ventilation, he developed multiple organ dysfunctions with fluid refractoriness and capillary leak. Acute liver failure secondary to severe dengue is a rare complication with an unfavorable outcome.